2021
DOI: 10.15252/embr.201949568
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐induced degradation of the persistent hepatitis B virus cccDNA form depends on ISG20

Abstract: Hepatitis B virus (HBV) persists by depositing a covalently closed circular DNA (cccDNA) in the nucleus of infected cells that cannot be targeted by available antivirals. Interferons can diminish HBV cccDNA via APOBEC3-mediated deamination. Here, we show that overexpression of APOBEC3A alone is not sufficient to reduce HBV cccDNA that requires additional treatment of cells with interferon indicating involvement of an interferon-stimulated gene (ISG) in cccDNA degradation. Transcriptome analyses identify ISG20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 87 publications
0
44
0
Order By: Relevance
“…5 D, top) showed increasing IFNβ expression over time in poly I:C but not in IVT mRNA transfected cells. We repeated the experiment with either 1000 ng IVT mRNA or poly I:C in differentiated HepaRG, a cell line which has a functional interferon pathway 33 , also demonstrating exclusive upregulation of IFNβ in poly I:C treated cells over time (Fig. 5 D, bottom).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…5 D, top) showed increasing IFNβ expression over time in poly I:C but not in IVT mRNA transfected cells. We repeated the experiment with either 1000 ng IVT mRNA or poly I:C in differentiated HepaRG, a cell line which has a functional interferon pathway 33 , also demonstrating exclusive upregulation of IFNβ in poly I:C treated cells over time (Fig. 5 D, bottom).…”
Section: Resultsmentioning
confidence: 90%
“…We here established the transfection of various cell lines with IVT mRNA as a suitable tool to study whether NTCP expression suffices to render non-hepatic cells permissive for HBV and how NTCP concentration determines the efficiency of HBV infection. IVT mRNA proved to be a powerful alternative to introduce a gene of interest into hard-to-transfect hepatoma cells or primary cells 33 . Thereby, higher transfection efficiency and protein expression levels can be achieved in differentiated HepG2 cells than using plasmid or adenoviral vectors without affecting cell viability or triggering cell-intrinsic immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications are associated with reduced transcription of pgRNA and subgenomic RNAs from the cccDNA minichromosome. In addition to regulating cccDNA transcription, recent studies suggested that IFN may induce degradation of cccDNA by inducing APOBEC3A and ISG20 ( 31 , 32 ). However, it remains unclear how efficient such a mechanism is in the liver and whether cccDNAs in distinct epigenetic states are similar or differ in their sensitivity to IFN and IFN-induced antiviral factors.…”
Section: Advantages and Mechanisms Of Ifn-α Treatment Against Chbmentioning
confidence: 99%
“…ISG20 can impair mRNA synthesis and protein translation of RNA viruses [ 83 , 84 ]. Potentially, ISG20 can also contribute to the restriction of HBV replication and degradation of HBV cccDNA by APOBEC3A [ 85 ].…”
Section: The Role Of Innate Immunity In Restricting Viral Replicationmentioning
confidence: 99%